Identifikasi Arsip Digital dengan Pendekatan Machine Learning - Danish Faiq Ibad Yuadi (Khazanah: Jurnal Pengembangan Kearsipan, 2023)
The development of archive digitization technology, especially cameras, is an advantage for archive users. On the other hand, the ease of falsifying by digitizing records for a particular purpose is a problem for archivists in authenticating digital records. The purpose of this study is to identify digital sources, especially cameras as one of the tools applied in the archive digitization process. The research methodology combines clustering and classification in machine learning to determine 6 brands of cellphone cameras. The total data used in this experiment is 2400 archived digital images. The experimental results show that the identification rate of classification accuracy is 99%. This shows that this study is very effective in determining the authentication of digital archives, especially determining the source of the camera.